Comparison of surface roughness of root cementum and orthodontically induced root resorption craters from high- and low-fluoridation areas: a 3D confocal microscopy study - Chelsea Mann; Lam L. Cheng; Sarbin Ranjitkar; Selma T. Elekdag-Turk; Tamer Turk; M. Ali Darendeliler (SpringerOpen, 2022)
Abstract Background Fluoride has a major role in strengthening the structure of enamel against acids. Despite differences between caries and root resorption processes, both events inherently involve acidic dissolution of dental tissues. The aim of the present study was to investigate the effects of water fluoridation levels on the surface roughness of root cementum and resorption craters. The findings provided more insight into the influence of fluoride on the surfaces of intact cementum surface and resorption craters. Methods Twenty-eight orthodontic patients were recruited from two cities in Turkey, with high (≥ 2 ppm) and low (≤ 0.05 ppm) water fluoridation. These patients needed bilateral maxillary first premolar extraction as part of their orthodontic treatment and were allocated into two study groups (n = 14 in each group) based on water fluoridation exposure level: the high-fluoride group (HF) and low-fluoride group (LF). 150 g of buccal tipping forces was applied to all maxillary first premolar teeth for 12 weeks with a beta-titanium spring which was reactivated every 4 weeks. All maxillary premolars were removed at the end of the experiment for surface roughness assessment using three-dimensional confocal microscopy and the associated software. The buccal root surface and the largest buccal resorption crater were investigated. Results Resorption craters were significantly rougher in LF group compared to HF group (p = 0.002). Craters were rougher than the intact root surfaces (p = 0.000). Cervical and apical regions were significantly rougher than the middle region (p = 0.000 and p = 0.024, respectively). Conclusions Higher water fluoridation level of ≥ 2 ppm resulted in significantly smoother root resorption craters than low water fluoridation level of ≤ 0.05 ppm when the teeth were subjected to 150 g of buccal tipping force. Fluoride seems to have a protective role at the interface of root resorption, and further mineral or histological studies may shed light on the exact protective process against root resorption.